KONSEP PENAFSIRAN HADITS MEMULIAKAN TAMU TERHADAP PERILAKU MASYARAKAT DI KECAMATAN BESULUTU KABUPATEN KONAWE - Irdawati Saputri (Jurnal Ushuluddin Adab dan Dakwah, 2019)
This study discusses "The Concept of Interpretation of Hadiths Glorifying Guests Against Community Behavior in Besulutu District, Konawe Regency". In discussing the author raised the subject of the problem: How do people understand the hadith about glorifying guests in Besulutu District, Konawe Regency. This issue is discussed by limiting it to two sub-problems: 1). How is the concept of interpretation of the Hadith concerning glorification based on the Hadith of the Prophet (peace be upon him), 2). How is the behavior of the people in applying the procedure of glorifying guests according to the Hadith of the Prophet. This study aims: to describe the public's understanding of the Hadith of the Prophet, concerning glorifying guests in Besulutu District, Konawe Regency. The method used in this study is a qualitative research method with a sociological approach, with data collection techniques namely, observation techniques (observation), interview techniques (interview) and documentation techniques. The results showed that the way to glorify guests in the District of Besulutu in Konawe District follows their respective races. Facts on the ground, people's understanding of the hadith glorifying guests is good enough, but the attitude that reflects community organization is very alarming. Do not want to consult and always impose their own will, lack of sense of solidarity among the people, being emotional and respectful behavior of others. After being criticized by the hadith, the History of Abu Hurairah in terms of its quality is based on the rules used that the hadith is saheeh, and can be used as proof. This study implies that the hadith of the Prophet, provided the basis for activities to honor guests. For the people of the District of Besulutu, Konawe Regency, they can do a way to glorify guests well according to the hadith of the Prophet Muhammad, the history of Abu Hurairah.